Automated Sequential Derivatization for Gas Chromatography-[Orbitrap] Mass Spectrometry-based Metabolite Profiling of Human Blood-based Samples - Jbebli, Akrem; Coufalíková, Kateřina; Zanaboni, Moira; Bergna, Manuela; Picenoni, Renzo; Klánová, Jana; Price, Elliott J (Bio-protocol, 2025)
Many small molecules require derivatization to increase their volatility and to be amenable to gas chromatographic (GC) separation. Derivatization is usually time-consuming, and typical batch-wise procedures increase sample variability. Sequential automation of derivatization via robotic liquid handling enables the overlapping of sample preparation and analysis, maximizing time efficiency and minimizing variability. Herein, a protocol for the fully automated, two-stage derivatization of human blood-based samples in line with GC-[Orbitrap] mass spectrometry (MS)-based metabolomics is described. The protocol delivers a sample-to-sample runtime of 31 min, being suitable for better throughput routine metabolomic analysis. Key features • Direct and rapid methoximation on vial followed by silylation of metabolites in various blood matrices. • Measure ~40 samples per 24 h, identifying > 70 metabolites. • Quantitative reproducibility of routinely measured metabolites with coefficients of variation (CVs) < 30%. • Requires a Thermo ScientificTM TriPlusTM RSH (or comparable) autosampler equipped with incubator/agitator, cooled drawer, and automatic tool change (ATC) station equipped with liquid handling tools. Graphical overview Workflow for profiling metabolites in human blood using automated derivatization.